Plataforma de simula??o para an?lise de desempenho do sensoriamento espectral baseado em autovalores para r?dios cognitivos - Anjos, Andr? Ant?nio dos (2012)
This dissertation presents a MATLABr-based simulation platform for assessing the performance of cooperative spectrum sensing in cognitive radio (CR) applications. Through the platform it is possible to evaluate the performance of the following eigenvalue based techniques: ED, ERD, and RLRT GLRT. The platform is flexible in evaluating a broad range of system parameters, such as: number of cooperating cognitive radios, number of samples collected by each RC, number of primary transmitters, signal-to-noise ratio, type of signal transmitted by the primary user, among others. It can be configured to consider a conventional model, in which no signal processing is performed by each cooperating CR, or to consider a more realistic approach in which CR signal processing tasks are taken into account. The presence of two distinct types of impulsive noise can also be considered in the analysis, which can be generated with different shape, intensity and frequency. One of the greatest advantages of the developed platform is that, besides it can represent a huge amount of scenarios, it can also be easily customized for a specific user application, since it was developed into well isolated and defined modules.